Patenting of agriculture biotechnology and food security: options and challenges. (1st January 2012) - Srivastava, S.P.
When corporations develop new agricultural biotechnology products or processes or new crop varieties, they often seek legal rights over the intellectual property these innovations represent. However, intellectual property protection in agriculture is considered controversial because it directly confronts pre-existing systems of agriculture management that were mostly based on free exchange and on public sector involvement. There are five main issues with respect to agriculture and intellectual property. Firstly, question of patenting of life forms whose expansion constitute one of the main vehicle for the increasing role of patents in agriculture. Secondly, it has to take into consideration plant breeder's rights and farmers' rights, the two agriculture specific framework that have progressively proposed as alternatives to a system based on the free sharing of knowledge and germplasm. Thirdly, rights of sovereign nations from where biological resources are being collected by developing and developed countries for bio prospecting. Fourthly, whether genetically modified food is safe for health, and does it take into consideration environmental safety or not. Lastly, can we use agriculture biotechnology as option for food security?